Macro-Financial Determinants of Electricity Power Loss in Uganda - Alex Twinomuhwezi; Benjamin Musiita; Frederick Nsambu Kijjambu (Journal of Economics and Behavioral Studies, 2025)
This study examined the macro-financial determinants of electricity power loss in Uganda, with objectives that looked at GDP per capita, inflation, lending rates, the real effective exchange rate, and energy investment in electricity power loss. This study adopted a time series quantitative methodology. The secondary data was collected from reliable sources such as the World Bank, the Bank of Uganda, and the Electricity Regulatory Authority, spanning 20 years. The research applied a VAR model to analyze the short-run dynamics of the variables under consideration. The data were first cleaned to handle heteroscedasticity issues and missing values. The study found some of Uganda's most significant determinants of electricity losses to be macro-financial factors such as inflation, GDP per capita differences, and energy investment. Inflation volatility increased power losses, as did differences in GDP per capita, while low investment in energy translated to inefficiency within the electricity sector. Lending rates inhibited the infrastructural development of energy and, hence, power distribution and transmission efficiency. Therefore, the study concludes that addressing these macro-financial factors- inflation control, efficient energy investment, and economic policies- minimizes losses of electricity power in Uganda. This study suggests focusing on inflation stabilization, attracting investment in the energy sector, controlling the lending rate, and upgrading energy infrastructure management for better efficiency in the overall Ugandan electricity system. In addition, addressing issues of exchange rates and modern energy distribution technologies is central to minimizing losses and promoting an efficient energy sector
Keywords: Electricity power loss; GDP per capita; Inflation; Lending rates; Real effective exchange rate; Energy investment.